PENERAPAN STRATEGI PEMBELAJARAN INQUIRY DENGAN PENDEKATAN CTL (CONTEXTUAL TEACHING AND LEARNING) UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA KELAS VIII-D SMPN 4 TAMBANG - Zulkifli Zulkifli (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Riau, 2018)
This research is based on the low learning outcome of mathematics students of grade VIII SMPN 4 Tambang.The purpose of this research is to improve the learning outcomes of mathematics through the application ofinquiry learning with CTL approach. This research was conducted in SMPN 4 Tambang with subject of classVIII-D students with 29 students. This classroom action research was started in early January 2017. Theresearch instrument consists of a teacher and student activity sheet instrument and a test of learning outcomes.Based on the results of research and discussion can be concluded that the strategy of inquiry learning with CTLapproach can improve student learning outcomes of mathematics on the subject matter of algebraic form inclass VIII-D SMPN 4 Tambang. On the basic score the number of students who reached the KKM as many as 14people (48.28%) with an average score of 58.79. In cycle I the number of students who reach the KKM of 19people (65.52%) with an average value of 65.69%. In cycle II the number reaching KKM is 25 people (86.21%).